2019
DOI: 10.1590/0037-8682-0103-2018
|View full text |Cite
|
Sign up to set email alerts
|

Hansen’s disease deformities in a high risk area in Mozambique: A case study

Abstract: Introduction: Hansen's disease is no longer a public health problem in Mozambique, since 2008 (incidence under 1 / 10,000 inhabitants). The country is one of the most affected in the world and Nampula province's Murrupula district (incidence 1.7 / 10,000) has a high deformity rate (22% in 2010). This study aimed to identify high deformity rate associated determinants and proposals for better health program results. Methods: This study involved a descriptive quantitative survey, systematic observation of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
1
5
0
1
Order By: Relevance
“…The mean delay in diagnosis in our study was 26.6 months, much shorter than described in China at 64.1 months or in Colombia at 35.5 months, but longer than in India at 23.2 months, in Brazil at 25.5 months and over 12 months observed in Mozambique in 2013. 12,25,[27][28][29] A recent study in Ethiopia using the PEP4LEP questionnaire reported a mean delay of 22.0 months. 30 The delay observed in our study was also shorter than the mean case detection delay of 31.4 months reported in a recent systematic review that collected data on leprosy cases across several low-endemic countries.…”
Section: Discussionmentioning
confidence: 99%
“…The mean delay in diagnosis in our study was 26.6 months, much shorter than described in China at 64.1 months or in Colombia at 35.5 months, but longer than in India at 23.2 months, in Brazil at 25.5 months and over 12 months observed in Mozambique in 2013. 12,25,[27][28][29] A recent study in Ethiopia using the PEP4LEP questionnaire reported a mean delay of 22.0 months. 30 The delay observed in our study was also shorter than the mean case detection delay of 31.4 months reported in a recent systematic review that collected data on leprosy cases across several low-endemic countries.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the identification of leprosy cases presents some difficulties and, many times, the clinical picture is confused with several other dermatoses, and late diagnosis is a serious problem associated with the disease, significantly increasing the risk of developing sequelae. [16][17] Moreover, the delay in diagnosis may be associated with misdiagnosis and prejudice related to the disease, which contributes to the delay in seeking treatment and to self-medication. [18][19] Souza20 , in a research carried out in the state of Bahia, emphasizes that although the prevalence of leprosy has decreased over the years, the disease keeps its chain of transmission active, evidenced mainly by the tendency to increase the proportion of multibacillary cases and the coefficient of new cases with grade II physical disability at the time of diagnosis, suggesting also that the diagnosis occurs late and that there is a high hidden prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…19,22 Early diagnosis and treatment initiated immediately contribute to prevent the evolution of leprosy to major disabilities. Thus, it is possible to break the epidemiological chain of transmission of the disease 17 and, consequently, the social stigma and discrimination against affected persons and their families. [25][26] In the scope of the action of active search for those who missed leprosy treatment, in the evaluation, the regions that had the highest percentage of follow-up also stood out, especially the Northeast (91.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the CDD of leprosy in countries like Bangladesh [20], Brazil [21][22][23], India [15], Nepal [24] and Paraguay [25]. However, literature on the delay in diagnosis in the cultural context of Ethiopia, Mozambique and Tanzania is lacking or outdated [26][27][28][29]. Although several questionnaires have been designed to determine the CDD of leprosy [23,24,30], a specific standardized questionnaire for multi-country use does not exist.…”
Section: Conclusion/significancementioning
confidence: 99%